Optimization of Total Phenol and Tannin Content and Biological Activity of Dittrichia graveolens (L.) GREUTER. - Souri, Mahsa; Shakeri, Alireza (Current Bioactive Compounds, 2020)
Background: Dittrichia graveolens (L.) is a strongly aromatic plant distributed in Mediterranean regions. This research concerns the optimization of the Total Phenolic Content (TPC) and the Total Tannin Content (TTC) of Dittrichia graveolens (L.) extracts using Response Surface Methodology for Ultrasound Assisted Extraction (UAE) and Microwave Assisted Extraction (MAE). Central Composite Design (CCD) was used to evaluate the effect of the solvent concentration and the extraction time, in different methods on TTC and TPC. The antioxidant activities and antibacterial activities were evaluated. Methods: The plant extracts were prepared using maceration, microwave and ultrasound assisted extraction. TPC and TTC were measured using Folin-Ciocalteu method. The antioxidant activities were studied using DPPH reagent and disc diffusion method was used to study the antibacterial activities. Results: This study showed the optimum condition for UAE was 49.96% methanol concentration and 11.2 min sonication, while for MAE was 55.44% methanol concentration and 2.26 min microwave extraction. It also indicated that MAE was the most effective method in comparison to UAE and maceration. The antioxidant activities of MAE extract (IC50=7.7mg/mL) were more than UAE extract (IC50=21.5mg/mL) and maceration (IC50=32.3mg/mL). Conclusion: As a conclusion, it was indicated that MAE was the most effective method. The higher total phenolic content caused higher antioxidant activities as MAE extract had the highest antioxidant activities. The antibacterial test showed the great potential of this plant as an antibacterial compound resource against different bacteria.
Keywords: phenol